Analisis Promosi Digital dan Citra Merek dalam Mendorong Keputusan Pembelian Produk Fashion Lokal - Septian, Yosef Cindi; Zahrah, Halimah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of the local fashion industry encourages companies to utilize digital promotions and build brand image to influence consumer purchasing decisions. Increasingly fierce competition demands marketing strategies that not only increase exposure but also shape positive consumer perceptions of brands. This study aims to analyze the influence of digital promotions and brand image on purchasing decisions for local fashion products. The research method used a quantitative approach with a survey technique through the distribution of questionnaires to 80 respondents. Data were analyzed using multiple linear regression with the help of SPSS software. The results showed that digital promotions and brand image have a positive influence on purchasing decisions, but partially neither showed a significant influence. Simultaneously, digital promotions and brand image also did not have a significant influence on purchasing decisions. These findings indicate that purchasing decisions for local fashion products are not only influenced by digital promotions and brand image, but also by other factors outside the research model. The results of this study are expected to serve as an academic reference and input for local fashion entrepreneurs in formulating more comprehensive marketing strategies.